PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TARI BAMBU PADA MATA PELAJARAN SEJARAH - Desmawati, Desmawati (TABULARASA, 2014)
This study aims to determine whether the use of cooperative learning model bamboo dance can increase interest in studying history subjects. This type of research is "Class Action Research", by using cooperative learning model bamboo dance. This study consisted of two cycles, the first cycle and second cycle respectively - each have 2 meeting. Based on observations made of 30 students there were 24 students (80%) who have an interest in learning about and 6 students (20%) who have a sufficient interest. Then on the first cycle has value - average 44 (55%), while in the second cycle is equal to 69 (87%). The results of the test cycle I to cycle II, a significant increase, thus it can be concluded that by implementing cooperative learning model bamboo dance can increase student interest in the subject of History major subject Karajaan Indonesia Hindu-Buddhist period in class XI SMA 9 Medan Academic Year 2013/2014.PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TARI BAMBU PADA MATA PELAJARAN SEJARAH